2014
DOI: 10.3390/laws3010141
|View full text |Cite
|
Sign up to set email alerts
|

Death Row Confinement and the Meaning of Last Words

Abstract: Life under sentence of death can be a transformative process. One measure of this transformation can be found in last words, which often highlight the humanity of condemned prisoners on the threshold of execution, in sharp contrast to popular conceptions of these prisoners as evil, remorseless, and irredeemable. Our reading of last words suggests that the transformation process can be best understood by examining the dominant contours of the death row experience, the most recent formative experience in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Last statements were a documented part of the execution process since 1388 in England. This practice was brought over to the Americas as a mainstream practice early in the 17th century (Johnson, Kanewske, & Barak, 2014). The practice continues today and is viewed as a de facto right of capitally punished inmates.…”
Section: Last Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Last statements were a documented part of the execution process since 1388 in England. This practice was brought over to the Americas as a mainstream practice early in the 17th century (Johnson, Kanewske, & Barak, 2014). The practice continues today and is viewed as a de facto right of capitally punished inmates.…”
Section: Last Statementsmentioning
confidence: 99%
“…The practice continues today and is viewed as a de facto right of capitally punished inmates. Last statements were previously manipulated in the media for public entertainment, but now statements are recorded by officials and are more objective and accurate (Johnson et al., 2014).…”
Section: Last Statementsmentioning
confidence: 99%
“…First, as the findings suggest, changes in the social context of the death chamber and the composition of witnesses may influence how death row inmates chose to represent themselves in their last statements. Thus, an ethnographic approach similar to that conducted by Johnson and his associates (Johnson et al 2012(Johnson et al , 2014 can shed further light on the social context of confinement, the physical and mental toll it takes on death row inmates, and the influence it may have on their last statements. Second, religious coping theory offers one explanation as to why death row inmates draw on religious themes for self-presentation during the imminent death experience.…”
Section: Discussionmentioning
confidence: 99%
“…Further demonstrating that religion was a prominent feature of the final statements, the authors uncovered other important religious themes, such as preaching (15.8 percent), praying for others (13.4 percent), gratitude toward God (7.5 percent), prayer unspecified (6.8 percent), asking for God's forgiveness (6.8 percent), and prayer for self (6.5 percent). As alluded to above, studies documenting the most common themes found in the last statement data generally conclude that the themes are unexpectedly positive (Goranson et al 2017;Hirschmüller and Egloff 2018;Shermer 2018;Upton et al 2017) which is remarkable given the dire circumstances that death row inmates find themselves in at the moment of imminent death (Johnson et al 2014).…”
Section: The Last Statements Of Death Row Inmatesmentioning
confidence: 91%
“…Taken together, the reviewed text analysis studies of executed death row inmates' last words demonstrated that they contained surprisingly more positive than negative emotional expressions, with final statements' content themes revolving most strongly around expressions of love and appreciation, messages to relevant social others, and religious beliefs (see also Ward, 2010 ; Johnson et al, 2014 , for general overviews). That is, prisoners' final statements spoken moments prior to death seemed to focus on aspects, including social connections and religion, that make life (and death) meaningful (see e.g., Smith, 2017 ).…”
Section: Analyzing the Phenomenon: Language Use In Last Words Before mentioning
confidence: 99%